The Influence Of Syariah Compliance And Customer’s Satisfaction Towards Muslim Purchase Behaviour Hotel Syariah in West Sumatera - Febrian Ananda; Efrida Yanti; Febrian Rafqi; Feri Ferdian (Universitas Katolik Widya Karya Malang, 2023)
This study aimed to analyze the influence of sharia compliance and customer satisfaction towards Muslim purchase behavior in sharia hotels in West Sumatra. This research uses a quantitative methodology with a causal associative approach. Muslim guests who have stayed at sharia hotels constitute the population, and a purposive sampling technique is used to determine the number of research samples. The sample size for this study was 99 Muslim guests who had stayed at a sharia hotel in West Sumatra. Partial Least Square Structural Equation Modeling (PLS-SEM) is the analytical method used. From the results of research that has been carried out, the variables of sharia compliance and customers satisfaction have a positive and significant effect on the purchase behavior of sharia hotels in West Sumatra. It can be said that based on this research, purchase behavior occurs if the hotel is compliant and guests feel satisfied during their stay, then guests will consider purchase behavior.